Bessel Beam Illumination Reduces Random and Systematic Errors in Quantitative Functional Studies Using Light-Sheet Microscopy - Müllenbroich, M. Caroline; Turrini, Lapo; Silvestri, Ludovico; Alterini, Tommaso; Gheisari, Ali; Tiso, Natascia; Vanzi, Francesco; Sacconi, Leonardo; Pavone, Francesco S. (Frontiers in Cellular Neuroscience, 2018)
Light-sheet microscopy (LSM), in combination with intrinsically transparent zebrafish larvae, is a choice method to observe brain function with high frame rates at cellular resolution. Inherently to LSM, however, residual opaque objects cause stripe artifacts, which obscure features of interest and, during functional imaging, modulate fluorescence variations related to neuronal activity. Here, we report how Bessel beams reduce streaking artifacts and produce high-fidelity quantitative data demonstrating a fivefold increase in sensitivity to calcium transients and a 20 fold increase in accuracy in the detection of activity correlations in functional imaging. Furthermore, using principal component analysis, we show that measurements obtained with Bessel beams are clean enough to reveal in one-shot experiments correlations that can not be averaged over trials after stimuli as is the case when studying spontaneous activity. Our results not only demonstrate the contamination of data by systematic and random errors through conventional Gaussian illumination and but,furthermore, quantify the increase in fidelity of such data when using Bessel beams.